Peripheral cytokine levels as novel predictors of survival in cancer patients treated with immune checkpoint inhibitors: A systematic review and meta-analysis - Mao, Xin-Cheng; Yang, Chun-Cheng; Yang, Ya-Fei; Yan, Lun-Jie; Ding, Zi-Niu; Liu, Hui; Yan, Yu-Chuan; Dong, Zhao-Ru; Wang, Dong-Xu; Li, Tao (Frontiers in Immunology, 2022)
Abstract Background Early identification of patients who will benefit from immune checkpoint inhibitors (ICIs) has recently become a hot issue in cancer immunotherapy. Peripheral cytokines are key regulators in immune system that can induce the expression of immune checkpoint molecules, however, the association of peripheral cytokines and the efficiency of ICIs remains unclear. Methods A systematic retrieve was conducted in several public databases from inception through February 3, 2022 to identify studies investigating association of peripheral cytokines (ie. IL-1β, IL-2, IL-2RA, IL-2R, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12, IL-15, IL-17, TNF-α, IFN-γ, TGF-β) and ICIs treatment. Survival data, including overall survival (OS) and/or progression-free survival (PFS) was extracted, and meta-analyses were performed. Results 24 studies were included in this analysis. The pooled results demonstrated that the pretreatment peripheral levels of IL-6 (univariate analysis: HR=2.53, 95%CI=2.21-2.89, P<0.00001; multivariate analysis: HR=2.21, 95%CI=1.67-2.93, P<0.00001) and IL-8 (univariate analysis: HR=2.17, 95%CI=1.98-2.38, P<0.00001; multivariate analysis: HR=1.88, 95%CI=1.70-2.07, P<0.00001) were significantly associated with worse OS of cancer patients receiving ICIs treatment in both univariate and multivariate analysis. However, high heterogeneity was found for IL-6 which might be attributed to region, cancer type, treatment method, sample source and detection method. Conclusion Peripheral level of IL-8 may be used as a prognostic marker to identify patients that yield inferior response for ICIs. More high-quality prospective studies are warranted to assess the predictive value of peripheral cytokines for ICIs treatment.